Effects of active video games on parental support among overweight and obese adolescents in China: a pilot study - Abu Saad, Hazizi; Mai, Yiqiang; Soh, Kim Geok (Human Resources Management Academic Research Society (HRMARS), 2024)
The purpose of this study is to explore the effect of AVG intervention on the parental support of overweight and obese male adolescents under a family-based parental involvement model. A cluster randomised controlled trial (C-RCT) was conducted with 12- to 14-year-old participants, divided into three groups: (1) Parental Involvement in Active Video Games (PIAVG), (2) Single Player Active Video Games (SPAVG), and (3) Control (watching TV-WTV). The intervention lasted for two weeks, during which changes in parental support levels were assessed at baseline and post-intervention. No significant changes were observed within the three groups. However, notably, the PIAVG group demonstrated slightly improvement in the measured outcomes than the WTV group in the inter-group comparison, but it has no statistical significance. The findings suggest that parental involvement in active video games enhances the effectiveness of such interventions, leading to better parent-child relationships among overweight and obese adolescents. This underscores the potential for family-based interventions to combat adolescent obesity in this population.